Research of sensitivity of detection method subband pause noise impact - Evgeny Georgievich Zhilyakov; Sergey Pavlovich Belov; Alexandra Alexandrovna Medvedeva (Наука. Инновации. Технологии, 2022)
The article presents a selection method pauses in speech communications through the use of sub-band analysis. sensitivity study was conducted using an additive blending of normally distributed noise. the probability of wrong decision-making have been identified in various respects noise / signal. The results indicate that the stability of the proposed method of sub-band to the effects of the additive noise.